Evaluation of the Frequency and Pathological Diagnosis of Vulvar Lesions Is it Associated with Vulvar Pruritus - If So, How Closely? - Omer Demir; Mirac Ozalp; Turhan Aran; Mehmet Armagan Osmanagaoğlu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Vulvar lesions are not well known to gynecologists and often cause difficulties in the differential diagnosis. In this study; we aimed to show the frequency of pathologic diagnosis of vulvar lesions and their relationship with vulvar pruritus.